2020
DOI: 10.3928/23258160-20200831-06
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Individualized and Navigated Microsecond Pulsing Laser for Acute Central Serous Chorioretinopathy

Abstract: BACKGROUND AND OBJECTIVE: A computational model has predicted parameters for using a navigated microsecond pulsing laser system to treat central serous chorioretinopathy (CSC). PATIENTS AND METHODS: A prospective, single-center, interventional case series was conducted for patients with acute CSC who were enrolled following screening and informed consent. Treatment involved laser pulse duration of 50 μs, 2.4% Duty Cycle, 100 μm spot size, and 10 ms puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been shown to increase the antioxidative potential [ 17 , 18 ] and to reduce the thickness of the Bruch’s membrane in an age-related macular degeneration (AMD) mice model [ 19 , 20 , 21 , 22 ]. Thus, sublethal RPE thermal treatment gained increasing attention as a new therapeutic option for different macular disorders, such as CSC, diabetic macular edema and AMD [ 20 , 23 ]. In particular, the PLACE trial and a recent meta-analysis demonstrated that SML may be considered as a competitive alternative to PDT for treating chronic CSC, and as the first-line treatment of chronic CSC [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown to increase the antioxidative potential [ 17 , 18 ] and to reduce the thickness of the Bruch’s membrane in an age-related macular degeneration (AMD) mice model [ 19 , 20 , 21 , 22 ]. Thus, sublethal RPE thermal treatment gained increasing attention as a new therapeutic option for different macular disorders, such as CSC, diabetic macular edema and AMD [ 20 , 23 ]. In particular, the PLACE trial and a recent meta-analysis demonstrated that SML may be considered as a competitive alternative to PDT for treating chronic CSC, and as the first-line treatment of chronic CSC [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%